Hundens parvovirus - Cederwall, Maija (2011)
Canine parvovirus is associated with two disorders: enteritis, which is common, and myocarditis, which is rare. Prominent clinical signs of parvovirus enteritis are vomiting, diarrhea and rapid dehydration. Canine parvovirus type 2 (CPV-2) is very contagious. When CPV-2 first emerged it had high rates of mortality, but later studies have shown that most infections are self-limiting and do not require veterinary care. Mortality rates vary greatly, and therefore it is important to determine risk factors for developing severe canine parvovirus enteritis. Parvovirus is dependent on dividing cells for replication. The enteric form is characterized by necrosis of the epithelium of the crypts in the small intestine. The severity of the lesions depends on how fast the onset of circulating antibodies occurs. Necrosis and depletion of lymphoid tissue is often seen, which can result in lymphopenia. Myocarditis can develop by infection in utero or in puppies less than eight weeks old. A few reports describe a neurologic form of canine parvovirus, but the absence of viral antigen suggests that the brain lesions are not induced by direct canine parvovirus infection. Since the virus is dependent on dividing cells to replicate, the cell turnover of the crypt epithelium has an important impact on the course of the disease. Rapid cell turnover in the intestinal crypt epithelium can be caused by concurrent infections or a change in diet, therefore the cell turnover is considered a risk factor in terms of the severity of clinical disease. There have been conflicting reports concerning the importance of secondary disease determinants, such as breed, sex and season. Doberman and Rottweiler have been identified as breeds more susceptible to developing canine parvovirus enteritis. The aim of this study is to summarize pathological changes that occur in canine parvovirus enteritis and to discuss risk factors associated with the disease. Parvovirus infection in dogs does not cause severe outbreaks of enteritis in Sweden today as a result of vaccination. Unexpected changes due to virus mutation or change in immunity of the canine population can have major consequences if there is no continuation of the research on CPV-2.